2023
DOI: 10.3390/biomimetics8040376
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Biomimetic Hybrid Meso- and Nano-Scale Surface Topography on Blood and Protein Recruitment in a Computational Fluid Dynamics Implant Model

Hiroaki Kitajima,
Makoto Hirota,
Kohei Osawa
et al.

Abstract: The mechanisms underlying bone-implant integration, or osseointegration, are still incompletely understood, in particular how blood and proteins are recruited to implant surfaces. The objective of this study was to visualize and quantify the flow of blood and the model protein fibrinogen using a computational fluid dynamics (CFD) implant model. Implants with screws were designed with three different surface topographies: (1) amorphous, (2) nano-trabecular, and (3) hybrid meso-spikes and nano-trabeculae. The im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The studies demonstrated that the CFD model is simple, low-cost, and useful to explore the new area of research in implant biology and, indeed, provided novel results to deepen the understanding of osseointegration. For instance, macroscopic implant morphology, such as the screw shape or implant threads, induces protein retention by slowing down blood flow in certain areas of the implant [41]. Compared with hydrophobic surfaces, superhydrophilic implant surfaces-where the contact angle of water θ is 0 • -effectively promote the recruitment of proteins to the implant interface [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The studies demonstrated that the CFD model is simple, low-cost, and useful to explore the new area of research in implant biology and, indeed, provided novel results to deepen the understanding of osseointegration. For instance, macroscopic implant morphology, such as the screw shape or implant threads, induces protein retention by slowing down blood flow in certain areas of the implant [41]. Compared with hydrophobic surfaces, superhydrophilic implant surfaces-where the contact angle of water θ is 0 • -effectively promote the recruitment of proteins to the implant interface [39,40].…”
Section: Introductionmentioning
confidence: 99%